2014
DOI: 10.1302/2046-3758.38.2000295
|View full text |Cite
|
Sign up to set email alerts
|

The use of MRI in pre-operative evaluation of anterior talofibular ligament in chronic ankle instability

Abstract: ObjectivesTo evaluate the applicability of MRI for the quantitative assessment of anterior talofibular ligaments (ATFLs) in symptomatic chronic ankle instability (CAI).MethodsBetween 1997 and 2010, 39 patients with symptomatic CAI underwent surgical treatment (22 male, 17 female, mean age 25.4 years (15 to 40)). In all patients, the maximum diameters of the ATFLs were measured on pre-operative T2-weighted MR images in planes parallel to the path of the ATFL. They were classified into three groups based on a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 21 publications
2
22
1
5
Order By: Relevance
“…Even if one of the subdivided ligaments presented as injured, we assessed deltoid ligament or syndesmosis as injured when analyzing the prevalence. For the purpose of this study, chronic injury to these ligaments was defined as thickening, thinning, irregularities, discontinuity, nonvisualization, signal alteration, loosening or elongation of the ligaments on MRI ( 9 10 ). Additionally, the relationship between the LCLC injury complexity (ATFL alone, both ATFL and CFL, all ligaments) ( Table 1 ) and the prevalence of accompanying deltoid or syndesmosis ligament injury was also evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…Even if one of the subdivided ligaments presented as injured, we assessed deltoid ligament or syndesmosis as injured when analyzing the prevalence. For the purpose of this study, chronic injury to these ligaments was defined as thickening, thinning, irregularities, discontinuity, nonvisualization, signal alteration, loosening or elongation of the ligaments on MRI ( 9 10 ). Additionally, the relationship between the LCLC injury complexity (ATFL alone, both ATFL and CFL, all ligaments) ( Table 1 ) and the prevalence of accompanying deltoid or syndesmosis ligament injury was also evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…MRI has the ability to display soft tissues and the advantages of noninvasiveness, rapid evaluation, multiplanar display, and no radiation damage. Numerous studies have reported that MRI examination has a high diagnostic value [ 7 9 ]. Kumar et al reported a sensitivity of ATFL tears of 60%, accuracy of 72%, and specificity of 87% [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…These symptoms result from the disturbance of the biomechanics of the connection between the foot and the shin. The majority of authors agree that surgical treatment, regardless of the method used, counteracts these changes (4,5,18). According to these authors, restoration of normal function to the ATFL improves the stability of the foot and restores normal gait, thus giving the patient a chance to return to intended physical activity (1,2,5,18,20).…”
Section: Discussionmentioning
confidence: 99%